Peran Social Media Use dalam Membangun Brand Awareness di Era Digital: sebuah kajian Literatur: : sebuah kajian Literatur - Prahasta, Luqman Rabbani (Maliki Interdisciplinary Journal, 2025)
This study analyzes the role of social media in enhancing brand awareness in the digital transformation era. Social media has revolutionized communication, interaction, and information access, becoming a crucial tool for companies in building their brands. This research examines how social media platforms, particularly Facebook, Instagram, Twitter, and TikTok, can be leveraged to establish and strengthen brand awareness. The focus includes the mechanisms of social media influence on consumer perception, the effectiveness of various content types and strategies, and the development of a framework for measuring and analyzing social media’s effectiveness in boosting brand awareness. A literature review methodology was employed, analyzing SINTA-indexed journals (2018-2024) with keywords "social media use" and "brand awareness". Findings reveal a positive correlation between strategic social media use and increased brand awareness. Visual content, influencer collaborations, and employee engagement were identified as key factors. This research provides practical recommendations for companies to optimize social media utilization for building brand awareness and achieving marketing objectives.